Structural, electronic, and dielectric properties of a large random network model of amorphous zeolitic imidazolate frameworks and its analogues. Issue 8 (28th January 2019) - Wang, Hailong; Li, Neng; Hu, Zhongbo; Bennett, Thomas D.; Zhao, Xiujian; Ching, Wai‐Yim
Abstract: The amorphous zeolitic imidazolate frameworks (a‐ZIFs) models and its analogues (with 918 or 810 atoms, respectively) are constructed based on a larger continuous random network (CRN) model of amorphous SiO2 (a‐SiO2 ) model. The atomic, electronic, and dielectric properties of these structures, which possess different metal nodes and organic linkers, are investigated by well‐defined density functional theory (DFT) calculations. The results suggest that all a‐ZIFs have ultra‐low dielectric constants and a large energy loss function (ELF), which suggests that they may be good candidates for electromagnetic absorptive materials. Most important, these a‐ZIFs models offer a base‐line model for other amorphous ZIFs for further research on models containing vacancies, defects, doping or under high pressure or high temperature. Abstract : The dielectric properties and atomic and electronic mechanism of four constructed amorphous ZIF (a‐ZIF) models with different metal nodes and organic linkers are calculated by welldefined DFT calculations. The results reveal that the four a‐ZIFs have ultra‐low dielectric constants ? (vary in a range between 1.76 and 2.22) and a large energy loss function (ELF), which suggests that these a‐ZIFs all are good candidates for magnetic absorptive materials in the future.